Creativity in Court‐Connected Mediation: Myth or Reality?. Issue 4 (October 2014) - Adrian, Lin; Mykland, Solfrid
<x xml:space="preserve">Abstract</x> In this study, we examined creativity in court‐connected mediation. We analyzed 129 mediated agreements from civil cases in Norway and Denmark and compared the outcomes with the parties' original claims to determine whether the agreement addressed only the disputants' demands or contained other elements. If the mediated agreements contained elements in addition to the original claims, we considered them to be "creative." We devised a creativity scale and found that approximately two thirds of the cases contained creative elements and one quarter of them contained more than five creative elements. We then sought to determine which aspects of the mediation promoted creativity by looking at a variety of mediation characteristics (length of mediation, characteristics of the parties, etc.). We found that lengthier mediations tended to feature more creativity as did cases that involved two private individuals rather than businesses. Cases whose issues involved inheritance as well as the division of property following divorce seemed to foster the highest levels of creativity. Finally, we found that the amount of money at issue also seemed to be relevant: the highest levels of creativity were found in cases in which more money was at stake. In this article, we also discuss the implications of our findings for future research, practice, and training.